2020
DOI: 10.1128/jvi.00205-20
|View full text |Cite
|
Sign up to set email alerts
|

RNase L Amplifies Interferon Signaling by Inducing Protein Kinase R-Mediated Antiviral Stress Granules

Abstract: Virus infection leads to activation of the interferon (IFN)-induced endoribonuclease RNase L, which results in degradation of viral and cellular RNAs. Both cellular and viral RNA cleavage products of RNase L bind pattern recognition receptors (PRRs), like retinoic acid-inducible I (Rig-I) and melanoma differentiation-associated protein 5 (MDA5), to further amplify IFN production and antiviral response. Although much is known about the mechanics of ligand binding and PRR activation, how cells coordinate RNA sen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 87 publications
3
74
3
Order By: Relevance
“…However, it may be important to note that viral dsRNA could not be detected within SGs in this infection model, which may indicate that SGs adopt an antiviral function as platforms for RIG-I or MDA5 activation only when they accumulate viral RNA [95]. Another study showed that disruption of SGs in IAV∆NS1and SeV-infected cells did not reduce but actually increased RIG-I-mediated IFN-β production [202], which is in direct contradiction with previous observations [242,263]. It is therefore still unclear whether the changes observed in the IFN response ensue from the disruption of SGs as a coordinating platform or are due to the immunomodulatory function of single SG components.…”
Section: Sgs a Platform To Initiate Ifn Signaling?contrasting
confidence: 86%
See 2 more Smart Citations
“…However, it may be important to note that viral dsRNA could not be detected within SGs in this infection model, which may indicate that SGs adopt an antiviral function as platforms for RIG-I or MDA5 activation only when they accumulate viral RNA [95]. Another study showed that disruption of SGs in IAV∆NS1and SeV-infected cells did not reduce but actually increased RIG-I-mediated IFN-β production [202], which is in direct contradiction with previous observations [242,263]. It is therefore still unclear whether the changes observed in the IFN response ensue from the disruption of SGs as a coordinating platform or are due to the immunomodulatory function of single SG components.…”
Section: Sgs a Platform To Initiate Ifn Signaling?contrasting
confidence: 86%
“…Recently, RNase L was reported to localize in SGs upon transfection of 2-5A. The resulting RNase L cleavage products were found to activate PKR, hence triggering SG formation and subsequent induction of IRF3-mediated IFN response [263]. Contradictory to these findings, earlier reports indicate that RNase L activity reduces PKR protein levels and eIF2α phosphorylation via destabilizing PKR mRNA [349].…”
Section: Oligoadenylate Synthase and Rnase Lmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, they could sequester ribosomes and thereby prevent translation of viral transcripts. On the other hand, translation of fragments could be detrimental to the host since ribosomes melt mRNA secondary structure (Mizrahi et al, 2018) and this structure in the fragments was suggested to be important for activating other dsRNA sensors that trigger interferon production and assembly of stress granules (Burke et al, 2019;Malathi et al, 2007;Manivannan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…RNase L could therefore be important for generally reshaping the transcriptome and translatome to enhance the response to viral infection. Intriguingly, the RNase L cleavage fragments themselves have been proposed to be important since they can activate dsRNA sensors, such as RIG-I, MDA5, and PKR, that lead to IFN production or shutdown of translation initiation (Malathi et al, 2007;Manivannan et al, 2020). It remains unknown whether the fragments themselves have additional roles, such as the ability to be translated into short peptides.…”
Section: Introductionmentioning
confidence: 99%